2018
DOI: 10.1155/2018/1985031
|View full text |Cite
|
Sign up to set email alerts
|

Role of “Second Look” Lymph Node Search in Harvesting Optimal Number of Lymph Nodes for Staging of Colorectal Carcinoma

Abstract: As with other malignancies, lymph node metastasis is an important staging element and prognostic factor in colorectal carcinomas. The number of involved lymph nodes is directly related to decreased 5-year overall survival for all pT stages according to United States Surveillance, Epidemiology, and End Results (SEER) cancer registry database. The National Quality Forum specifies that the presence of at least 12 lymph nodes in a surgical resection is one of the key quality measures for the evaluation of colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This is the largest study to evaluate the effectiveness of lymph node resampling in CRC, and the first study to use a cohort exclusively comprising cases with initial yields of <12. Two previous studies assessed lymph node resampling; however, the samples included specimens that required additional sections for any indication, or cases for which resampling was performed even with initial yields of ≥12 41,42 . Because of the application of stricter criteria, the findings of the present study better reflect the utility of lymph node resampling when it is performed in accordance with the recommended guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…This is the largest study to evaluate the effectiveness of lymph node resampling in CRC, and the first study to use a cohort exclusively comprising cases with initial yields of <12. Two previous studies assessed lymph node resampling; however, the samples included specimens that required additional sections for any indication, or cases for which resampling was performed even with initial yields of ≥12 41,42 . Because of the application of stricter criteria, the findings of the present study better reflect the utility of lymph node resampling when it is performed in accordance with the recommended guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…All these parameters, separately or in combination, have been evaluated considering their impacts on the LN yield. Quality of the pathological examination is another essential parameter that has an impact on the number of retrieved LNs [19][20][21]. In the presence of adequate proximal and distal borders, a detailed and careful pathological examination may lead to an increased yield.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of adequate proximal and distal borders, a detailed and careful pathological examination may lead to an increased yield. Although the second-look LN search caused considerable increases in the LN counts and number of cases with at least 12 LNs, its benefit on the accurate staging was limited [20]. Becerra et al [19] reported a large variation particularly between pathologists in suboptimal LN examination following colectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations